Implementing Lean : Twice the Output with Half the Input! - Protzman, Charles; Whiton, Fred; Protzman, Dan (Boca Raton, FL : Productivity Press, 2018)
Everyone has heard the phrase about doing twice the work in half the time, but instead of focusing only on time, this book focuses on driving increased output with consistently less input. Implementing Lean: Twice the Output with Half the Input! teaches readers not only about Lean and its major concepts, but it drives the leader toward implementing a true Lean system. The authors have used the methodologies in this book everywhere from hospitals to service industries to manufacturing plants in order to impact businesses by providing proven principles, techniques, and approaches that yield substantial improvement to any business, small or large, in any sector. Learn about the benefits of implementing Lean in your company as the authors walk you through the major components as well as show you how to implement them. This guide is already being used by Lean Practitioners every day on shop floors to educate and refresh how tools are used in real-world applications.
1. The Lean Business Delivery System -- 2. Learning from Toyota: Lean Philosophy and Foundations -- 3. Lean Accounting and Accounting for Lean -- 4. Our Misguided Allegiance to the Batching Paradigm -- 5. Waste versus Efficiency -- 6. The Lean Assessment -- 7. Lean and Change Management -- 8. Transitioning to a Lean Leader -- 9. Getting Ready to Implement a Lean System -- 10. BASICS Model: Baseline Data and VSM -- 11. BASICS: From AssessProduct-Flow Analysis (TIPS) -- 12. BASICS Model Assessment: Workflow AnalysisFollowing the Operator (Staff) -- 13. BASICS Model AssessmentSMED: Single-Minute Exchange of Die (SMED) -- 14. The BASICS Model: Suggest Solutions -- 15. Creating Standard Work -- 16. System-Based Lean Implementation Approach Utilizing the BASICS ModelKaikaku -- 17. Hoshin Kanri: Strategic Planning/Policy Deployment -- 18. Lean Transactional Processes -- 19. Lean Machine Shops and Job Shops -- 20. Visual Management -- 21. Heijunka, Planning and Scheduling, Sequencing Activities, Mixed Model -- 22. Lean +QDIP, and Huddles -- 23. Lean Materials -- 24. Lean and EngineeringDFM/A -- 25. Mistake-Proofing -- 26. Total Productive Maintenance -- 27. BASICS Model: Check and Sustain
OCLC-licensed vendor bibliographic record.
Keywords: Lean manufacturing; BUSINESS & ECONOMICS -- Workplace Culture; BUSINESS & ECONOMICS / Quality Control; BUSINESS & ECONOMICS / Workplace Culture